Identification and genomic characterization of a novel species of feline anellovirus. Issue 1 (December 2016) - Zhang, Wen; Wang, Hua; Wang, Yan; Liu, Zhijian; Li, Jingjiao; Guo, Lianghua; Yang, Shixing; Shen, Quan; Zhao, Xiaoying; Cui, Li; Hua, Xiuguo
Abstract Here, a novel feline anellovirus strain (named FelineAV621 and GenBank no. KX262893) was detected in two cats with diarrhea. The complete genome of FelineAV621 is 2409 nt long with a G+C content of 56.67 %, including three open reading frames (ORFs). Phylogenetic analysis based on the amino acid sequence of the putative capsid protein (ORF1) indicated that FelineAV621 belonged to a novel anellovirus species inside a clade containing the seal anellovirus, canine TTVs, and porcine TTVs, but was distant from all the previous feline anelloviruses.